CORRUPTION AS A SYSTEMIC PHENOMENON − Political System, Structure of Government, Institutions, Policies – - Madžar, Ljubomir (International Journal of Economic Practice and Policy, 2015)
The subject of these considerations is the institutional reality in Serbia, as a general backdrop and a determinant of corruption. It is demonstrated that Serbia, being ethnically, religiously and culturally heterogeneous, is predestined to be extremely differentiated in the political sense, too. Serbia is therefore equally preordained to be governed by extremely inefficient coalition governments formed by and leaning on extraordinarily wide political coalitions, rarely comprising less than ten parties. Coalition governments take a long time and lots of efforts to form, they have difficulties in reaching mutually acceptable and consistent courses of action, they face hazards of their internal conflicts. In addition, they are forced to satisfy a wide multitude of frequently opposed interests. They are easy to dismiss and very uncertain and volatile in their acts and policy orientations. Each coalition partner can blackmail the rest of the government and can, within wide limits, obtain whatever is highlighted as a „legitimate“requirement. The legislature, executive and judiciary branches of government are not functionally separated and the mechanism of checks and balances does not operate. Power is vertically divided instead, with parties as members of the ruling coalition holding all layers of all three powers within segments of governments which are assigned to them by the coalition compact. For instance, the party which has agriculture within its command, controls all institutions associated with agriculture at all hierarchical levels of political and administrative control. The parties in government have extremely strong power position: they cannot be dispensed with by the government and can even hardly be criticized. On the other hand, the government as a whole is sadly inefficient in performing its functions and vacillating in its policy stands. In sum, it is strong where its strength is not socially desirable and weak where its potency and resilience are mostly needed. In such institutional circumstances – with far from completed regulatory structure and institutional vacua pervading all over – the struggle against corruption is uneven and hazardous, while the existing institutions created to fight it have to design well thought out and farsighted strategies in order to achieve any success.